IMPLEMENTASI KERJA SAMA UNIVERSITAS PADJADJARAN DENGAN INSTANSI PEMERINTAH DALAM MENINGKATKAN EMPLOYABILITY MAHASISWA DI PUSAT PENGEMBANGAN KARIER UNIVERSITAS PADJADJARAN - Rafsanjani, Rio Patti; Rudiana; Adinda, Jovanscha Qisty (Jurnal Governansi, 2025)
Rapid technological developments have significantly changed the landscape of the world of work, causing a shrinking job market and increasing competition in the labor market. The employability of students is a key factor in determining their readiness to compete in an increasingly dynamic world of work. This study aims to analyze and describe the implementation of cooperation between Padjadjaran University and government agencies in improving student employability. The research method used is applied research with a qualitative descriptive approach, and the data source in this study was obtained through direct interviews with the Head of the Career Development Center of Padjadjaran University. The results of the study indicate that the communication process in the implementation of cooperation has been running effectively by prioritizing aspects of transmission, clarity, and consistency. Unpad has managed human and financial resources well, involving PPK staff, interns, and additional staff from government agencies. Padjadjaran University shows commitment and positive responses when establishing cooperation with various partners. The bureaucratic structure, including SOPs and division of tasks between units, has been running quite well with assignments that are in accordance with the capabilities of each individual. However, the process of submitting cooperation through formal bureaucracy takes a long time, so proactive communication is needed in the form of monitoring and confirmation of the status of the application until the implementation of the activity. Another novelty of this study lies in identifying administrative and technical barriers to implementing cooperation between Unpad and government agencies. This study also provides an in-depth analysis of strategies that can be applied to optimize the effectiveness of cooperation programs to improve student readiness in the world of work.